Immunohistochemical Expression of Myeloid Differentiation Adaptor Protein-88(MYD-88 )and Toll like Receptor (TLR-4) in Human Leiomyomas - Huda Saddon Jassim; Ali Yhea Salman; Sajid saad mohanned (Institute of Medico-legal Publications Pvt Ltd, 2021)
Leiomyomas are the most common benign tumor of the female reproductive tract. The aim of this study wasto explore the role of TLR4/ MYD-88signaling pathway in the pathogenesis of leiomyomas. Benign natureand smooth muscle origination of leiomyomas was easily documented via histological examination, in thiscross-sectional study of 20 conventional leiomyomas cases TLR4/ MYD-88 antibody status was positive in90% for TLR-4 and in 95% for MYD-88 of leiomyomas. Leiomyomas were stained with TLR4/ MYD-88marker more than those in normal myometrium cases (P<0.001). In conclusion leiomyomas growth may beassociated with TLR4 and MyD88 expression